Beyond individualism : the challenge of inclusive communities - Rupp, George (Religion, culture, and public life., 2016)
In many places around the globe, relations between ethnic and religious groups that once coexisted more or less amicably are now fraught with aggression and violence. This troubling trend has profound international implications, threatening efforts to protect the Earth's ecosystem and narrow the gap between rich and poor. Underscoring the need for immediate action, George Rupp urges the secular West to reckon with the continuing power of religious conviction and seek ways to embrace the full extent of the world's diversity.